Epidemiological Analysis of 5,595 Procedures of Endovascular Correction of Isolated Descending Thoracic Aortic Disease Over 12 Years in the Public Health System in Brazil (Clinics, 2021)
OBJECTIVES: In Brazil, descending thoracic aorta disease, including aneurysms and dissections, is managed preferentially by endovascular treatment, owing to its feasibility and good results. In this study, we analyzed endovascular treatment of isolated descending thoracic aortic disease cases in the Brazilian public health system over a 12-year period.METHODS: Public data from procedures performed from 2008 to 2019 were extracted using web scraping techniques to assess procedure type frequency (elective or urgency), mortality, and governmental costs.RESULTS: A total of 5,595 procedures were analyzed, the vast majority of which were urgent procedures (61.82% vs. 38.18%). In-hospital mortality was lower for elective than for urgent surgeries (4.96 vs.10.32% p=0.008). An average of R$16,845.86 and R$20,012.04 was paid per elective and emergency procedure, respectively, with no statistical difference (p=0.095).CONCLUSION: Elective procedures were associated with lower mortality than urgent procedures. There was no statistically significant difference between elective and urgent procedures regarding costs.